Anggah-Ungguhing Basa Bali for Young Generation in Bali, A Challenge in the Future - I Kadek Widiantana (IAHN-TP Palangka Raya, 2023)
Anggah-ungguhing Basa Bali is a level of language in Balinese, including basa bali alus, basa madia, basa kepara and basa kasar. The thing that is a big challenge in the midst of globalization, especially for the younger generation, is the variety of basa Bali alus. In the current era, the understanding of basa Bali alus among the younger generation in Bali has decreased. This research is a library research that originates from books and previous studies. Through this research found if the supporting factors for the existence of the anggah-ungguhing basa Bali include regulations from the government and and Balinese cultural traditions that still require the use of basa Bali alus, especially in formal languages. The inhibiting factors include, the younger generation perceives the anggah-ungguhing basa Bali as difficult, the younger generation prefers communicative languages, the Balinese language is not fully the mother tongue of the Balinese people, and there are leaks in language diglossia. Teaching Balinese at an early age in the family is very important, so that Balinese really becomes the mother tongue for the Balinese people.